A atuação da coordenação pedagógica na constituição identitária do professor por meio da formação continuada em uma instituição confessional - Cordeiro, Ana Aparecida Antunes (2024)
The theme of pedagogical coordination and teachers’ professional development is one of the topics discussed by several theorists of education. Also, teachers’ identity constructions is a relevant academic issue. The theme of this investigation is to understand and analyze the professional development actions of pedagogical coordinators at Rede Santa Paulina. This research used documents of the school, legal educational documents and important authors who discuss pedagogical coordination and teachers’ identity. The participants were three pedagogical coordinators who work in two schools of the private confessional school system. To discuss teachers’ identity, it is necessary to consider how long these coordinators work in the system and as coordinators, and how they work towards helping teachers take charge of their attributions, turning them into belonging, even when they do not follow catholic creeds. Theoretical framework was rooted in studies of pedagogical coordination, teachers professional development and teachers’ identity construction. Through qualitative research, semi-structured interviews were used. Data analysis used prose analysis. This research concluded that the charisma of the institution plays an important role, because it is the source and origin of teachers’ concepts, values and ways of acting. Results showed to the need of a professional development plan within the school system to provide more effective meetings and to enhance the bonds between professionals and the institution, aiming to develop and improve learning. Professional recognition and appreciation were highlighted, although not being considered enough to maintain professional loyalty to the institution. The coordinators reinforced the importance of improving cross-curricular projects, and that it is crucial to establish relationships with the families, as it serves as a strength to both schools, despite the challenges. We also concluded that the pedagogical coordination is a relevant asset for transforming and improving the school environment through its strategic actions on teachers’ identity construction, in order to overcome challenges and promote quality and meaningful professional development meetings, which also requires favorable times and spaces